Bilateral Hemiarthroplasty in a Patient with Below-Knee and Above-Knee Amputations: A Case Report. Issue 1 (13th January 2016) - Arango, Dillon; Tiedeken, Nathan C.; Gershkovich, Grigory; Shaffer, Gene
Abstract : Case: This case involved a sixty-two-year-old male patient with bilateral femoral neck fractures that occurred six months apart in the setting of bilateral lower-extremity amputation. Hemiarthroplasty was performed at each presentation, with the use of a standard femoral stem on the right side and a short stem on the left. At the time of follow-up, the patient had returned to his preoperative ambulatory status. Conclusion: This case report illustrates successful bilateral hemiarthroplasty in a patient who had previously undergone bilateral lower-extremity amputation, with use of an implant with a short stem for the limb with above-knee amputation.